RANCANG BANGUN PROTOTYPE SISTEM MONITORING PENGATURAN SUHU DAN KELEMBAPAN PADA BANGUNAN RUMAH WALET BERBASIS IOT - Sidabutar, Aprillius Mawendra; Nurussa’adah, n/a; Asmungi, Gaguk (Jurnal Mahasiswa TEUB, 2024)
The walet is a species of bird that provides many health benefits through its nest made of saliva, such as accelerating cellregeneration, strengthening the immune system, and aiding the digestive system. The high selling price of the bird's nest hasprompted many people to cultivate it. Temperature and humidity are important factors in walet cultivation, with the optimaltemperature ranging between 26-29°C and humidity between 80-95%. Bojonegoro district, East Java, is famous for its oil drillingactivity that increases temperature and lowers environmental humidity, making it unsuitable for walet cultivation. Therefore, there is a need for a monitoring system capable of maintaining the temperature and humidity of the walet house at ideal levels. This monitoring system works automatically without human intervention, saving time and effort. The objective of this research is to design and build a prototype temperature and humidity monitoring system based on the Internet of Things (IoT) for walet houses in Bojonegoro District. It is expected that the implementation of this system can significantly improve the quality and quantity of walet nests. Keywords: walet cultivation, temperature and humidity monitoring, Internet of Things (IoT), automatic system.